Failure Analysis and Optimization of Main Engine Cooling System Maintenance on a Fishing Vessel: A Case Study of KM. God Bless 08 - Muaimin Jufri, Irvan (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
Abstract The cooling system on a ship's main engine plays a crucial role in maintaining operational temperature stability but often encounters technical issues that can degrade engine performance and risk damage to critical components. This study identifies the factors causing failures in the cooling system of the main engine on KM. God Bless 08, particularly in the heat exchanger and pipeline components. Data were collected through field observations and direct measurements of freshwater and seawater temperatures at various operational points of the engine. The analysis revealed that the cooling system's performance significantly declined due to dirt deposits and corrosion in the capillary pipes, which hindered the efficiency of heat exchange between seawater and freshwater. The findings of this research provide insights for optimizing the cooling system through regular maintenance and component cleaning, essential for preventing overheating and improving the efficiency of the ship's main engine operations.